Outcome of Yag Laser Vitreolysis in Symptomatic Vitreous Floaters at Tertiary Care Hospital Karachi - Rajani, M. Asghar; Qureshi, Faisal Murtaza; Hilal, Mudassir; Majid Khan, Burhan Abdul; Memon, Riaz (Indus Journal of Bioscience Research, 2025)
Background: Vitreous floaters are a common ocular condition that can significantly impair quality of life. Nd:YAG vitreolysis is a minimally invasive procedure that has shown promise as a treatment for symptomatic floaters. Objective: To assess the clinical outcomes of Nd:YAG vitreolysis in terms of symptom improvement, visual disturbance, and complications. Methods: A descriptive study was conducted at the Retina Clinic of POB Eye Hospital. The Nd:YAG procedure was performed by an experienced ophthalmologist fellow, and outcomes were assessed at 8 weeks post-treatment. Data analysis was performed using SPSS version 22.0. Results: Out of the 113 patients, 28% reported complete improvement, 48% had partial improvement, and 24% showed no improvement in floaters. Visual disturbance improved from a mean of 20/70 pre-treatment to 20/40 post-treatment in 70% of patients. Stratification by comorbidity revealed that patients without hypertension or diabetes mellitus had higher rates of complete improvement. One subject developed retinal detachment 1 week after the procedure, which was managed with pars plana vitrectomy, resulting in a restored visual disturbance of 6/9. Conclusion: Nd:YAG vitreolysis is an effective and safe treatment for symptomatic vitreous floaters, with most patients experiencing significant improvement in symptoms and visual disturbance. However, careful monitoring is required, as complications such as retinal detachment, though rare, can occur.